POTENCY AND DEVELOPMENT STRATEGY OF SPOTTED BUFFALO IN SANGGALANGI SUBDISTRICT, NORTH TORAJA DISTRICT, SOUTH SULAWESI - Komariah, K.; Setyono, D.J.; Afandi, A. (Diponegoro University, 2012)
The aim of this research was to analyze the reproduction performances, potency and developmentstrategy of Torajan's spotted buffalo. This research was done from July to September 2010 inSanggalangi’ subdistrict, North Toraja district, South Sulawesi. Purposive sampling was applied toobserve data. The primary data were taken by purposive sampling method and collected by interview of90 farmers. Results showed that sex ratio of male-female was 3:2. The first estrus was 2.48 years old,the estrus period was 23 hours and the oestrus cycle was 19 days. The first mating was 2.87 years oldwith the conception period about 387 days. Furthermore, the first partus was at 3.74 years old, calvinginterval was 2 years. Calving rate and calf crops were relatively high. Calf crops were 77%, pre weaningmortality was 2.35%. Service per conception (S/C) was 1.85 and conception rate (CR) was 86.5%. Themost livelihoods in North Toraja is farmer. Spotted Buffalo population declined 24.31 % per year.SWOT analysis showed that score for internal factor was -0.25, whereas external factor was 2.25. It wasshowed that the sub-district Sanggalangi is in turnaround condition, so the development strategy ofTorajan’s spotted buffalo has to minimize the weakness and reached the opportunities.